IDENTIFICATION OF LEADING ECONOMIC SECTORS AND DEVELOPMENT CHALLENGES IN INDONESIA - Loso Judijanto (Review of International Economy and Finance, 2025)
This study aims to identify the main economic sectors and development challenges facing Indonesia in 2025 using a literature review method. The results of the study indicate that Indonesia's economic structure is dominated by the service, manufacturing, and agriculture sectors, with the service sector being the largest contributor to the Gross Domestic Product (GDP). However, Indonesia still faces various major challenges, including dependence on primary commodities, regional and income disparities, uneven infrastructure and human resource quality, and limitations in innovation and technology mastery. Additionally, external factors such as global demand fluctuations and climate change challenges further complicate the development process. This study emphasises the importance of strategic reforms and cross-sectoral collaboration to create inclusive, resilient, and sustainable economic growth in the future.